Parasexual and Sexual Reproduction in Arbuscular Mycorrhizal Fungi: Room for Both. Issue 7 (July 2020) - Yildirir, Gökalp; Malar C, Mathu; Kokkoris, Vasilis; Corradi, Nicolas
Abstract : Arbuscular mycorrhizal fungi (AMF) harbor thousands of nuclei in a large syncytium at all times. Although mating processes have not been observed in AMF, their cells and genomes show many signatures of sexual reproduction. Here, we describe how some of these signatures could also arise from parasexual processes in these widespread plant symbionts. As such, parasexual and sexual evolution could both be at play in generating nuclear diversity in AMF.